Microporous Polymer Membranes: Molecular Stents Enhanced Solvent‐Accessibility for Organic Solvent Transport - Shuang Guo; Chuanjie Fang; Jiaqi Li; Xiaohe Wang; Weilin Feng; Hukang Guo; Ming Xie; Yongbing Zhuang; Young Moo Lee; Liping Zhu (Advanced Science)
Abstract Microporous polymer membranes with high solvent permeability are pivotal for upgrading molecular separations in organic solvents, but this remains challenging due to numerous sub‐0.4 nm ultra‐micropores resulting from local tight packing, which limit solvent‐accessibility. Herein, a microporous polyimide with high intrinsic free volume [PI‐TB‐NDI, naphthalenediimide (NDI) and Tröger's base (TB)] is synthesized for organic solvent nanofiltration. The resulting polymer showed high free volume because of fused aromatic rings and a twisted structure. Aromatic rings enhanced solvent resistance due to strong molecular interaction, but increased detrimental local tight packing as well. To suppress local tight packing without compromising the molecular interactions vital for stability, an ortho‐methyl group is deliberately introduced onto the TB unit to increase both intra‐ and inter‐molecular steric hindrance, imparting an H‐shaped TB‐NDI‐TB molecular stent. On the introduction of ortho‐methyl groups, the sub‐0.4 nm ultra‐micropores are enlarged to ultra‐micropores (0.6–0.7 nm) to give the membrane with rich solvent‐accessible sub‐nanochannels. This resulted in an unprecedented enhancement of solvent permeability, with ethanol permeability 2‐8 times greater than that of state‐of‐the‐art polymer membranes with similar selectivity. These findings advance the design strategy of microporous membranes with well‐tailored free volume without post‐treatments, enabling upscaling and efficient separation of precious species in organic solvents.